1995
DOI: 10.1063/1.115371
|View full text |Cite
|
Sign up to set email alerts
|

Addition of N2 as a polymer deposition inhibitor in CH4/H2 electrocyclotron resonance plasma etching of Hg1−xCdxTe

Abstract: An approach is presented which eliminates the problems caused by hydrocarbon polymer deposition in etching compound semiconductor with CH4/H2 based plasmas. We find that atomic nitrogen, created by the addition of N2 to the plasma, inhibits polymer deposition in the chamber and on the sample. Atomic nitrogen has several beneficial effects; the elimination of polymer precursors, the reduction of the atomic hydrogen concentration, and a potential increase of methyl radical concentration. It is also demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…13 Hydrogen in atomic or ionized form chemically volatilized tellurium from both the HgTe and CdTe sublattices leaving the metal constituent (Hg or Cd) to be physically sputtered by the argon. [8][9][10]13 From the poor surface morphology we obtain from the ICP process results, we deduce that the ICP process is H rich. This is reasonable, because the lower frequency ICP is more efficient at cracking hydrogen.…”
Section: Effect Of Gas Ratiomentioning
confidence: 98%
See 1 more Smart Citation
“…13 Hydrogen in atomic or ionized form chemically volatilized tellurium from both the HgTe and CdTe sublattices leaving the metal constituent (Hg or Cd) to be physically sputtered by the argon. [8][9][10]13 From the poor surface morphology we obtain from the ICP process results, we deduce that the ICP process is H rich. This is reasonable, because the lower frequency ICP is more efficient at cracking hydrogen.…”
Section: Effect Of Gas Ratiomentioning
confidence: 98%
“…[1][2][3][4] Several studies have also reported the effect of high density ''dry'' ECR plasmas on HgCdTe epitaxial properties. [5][6][7][8][9][10][11][12][13][14] Most ICP plasma processing results have been empirically based. 4,7,14 However, ICP plasma processing has become the industrial standard for HgCdTe delineation and via formation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, ICP plasma processing, used in HgCdTe, is still maturing and continued research is needed. 4,7,14 ICP plasma processing may also be used to replace conventional wet chemical clean-up, and even be used in the surface preparation for epitaxy of II-VI materials.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4] Several studies have also reported the effect that high-density ''dry'' electron cyclotron resonance (ECR) plasmas have on HgCdTe epitaxial properties. [5][6][7][8][9][10][11][12][13][14] However, ICP plasma processing, for use in HgCdTe, is still maturing and continued research is needed. 4,7,14,15 ICP plasma processing may also be used to replace conventional wet chemical clean-up, and can even be used in the surface preparation for epitaxy of II-VI materials.…”
Section: Introductionmentioning
confidence: 98%